2020
DOI: 10.4085/15-20
|View full text |Cite
|
Sign up to set email alerts
|

Submaximal Force Steadiness and Accuracy in Patients With Chronic Ankle Instability

Abstract: Context: Patients with chronic ankle instability (CAI) have demonstrated sensorimotor impairments. Submaximal force steadiness and accuracy measure sensory, motor, and visual function via a feedback mechanism, which helps researchers and clinicians to comprehend sensorimotor deficits associated with CAI. Objective: To determine if participants with chronic ankle instability experience deficits in hip and ankle submaximal force steadiness and accuracy compared to healthy controls. Design: A case-controlled stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…As we hypothesized, the CAI group showed worse eversion steadiness than the coper and control groups. The results align with a previous study that CAI patients showed worse force steadiness than healthy controls 12 . Rice et al 5 have previously assumed that increased errors in force steadiness and accuracy represent impaired proprioceptive function, altered spinal interneuron modulation of motor‐neuron firing, and altered motor‐unit recruitment.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…As we hypothesized, the CAI group showed worse eversion steadiness than the coper and control groups. The results align with a previous study that CAI patients showed worse force steadiness than healthy controls 12 . Rice et al 5 have previously assumed that increased errors in force steadiness and accuracy represent impaired proprioceptive function, altered spinal interneuron modulation of motor‐neuron firing, and altered motor‐unit recruitment.…”
Section: Discussionsupporting
confidence: 91%
“…Rice et al 5 have previously assumed that increased errors in force steadiness and accuracy represent impaired proprioceptive function, altered spinal interneuron modulation of motor‐neuron firing, and altered motor‐unit recruitment. In addition, a recently published article reported that impaired force steadiness and accuracy may be due to impaired proprioceptive function that has been shown in individuals with CAI patients 12 . The literature has widely reported that CAI patients show impaired proprioceptive function, 2 which is a crucial factor for people to perform appropriate neuromuscular control 21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations